1993
DOI: 10.1073/pnas.90.8.3574
|View full text |Cite
|
Sign up to set email alerts
|

Platelet factor 4 binds to interleukin 8 receptors and activates neutrophils when its N terminus is modified with Glu-Leu-Arg.

Abstract: Amino

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(115 citation statements)
references
References 40 publications
5
110
0
Order By: Relevance
“…Chemokine PF4, which carries DLS (or DLQ) in these positions, fails to attract neutrophils. Addition of ELR residues to an N-terminally truncated PF4 increases its chemotactic potential for neutrophils (14). In vIL-8, DKR, a putative hybrid motif of ELR and DLS, is present in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine PF4, which carries DLS (or DLQ) in these positions, fails to attract neutrophils. Addition of ELR residues to an N-terminally truncated PF4 increases its chemotactic potential for neutrophils (14). In vIL-8, DKR, a putative hybrid motif of ELR and DLS, is present in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The ELR ϩ CXC chemokines mediate their proangiogenic effects through a common receptor, CXCR2, which is predominantly found on vascular endothelial cells and neutrophils (16,17). Furthermore, we recently found that loss of CXCR2 inhibited tumor growth and angiogenesis in a murine model of lung cancer (18).…”
Section: R Enal Cell Carcinoma (Rcc)mentioning
confidence: 99%
“…In CXC chemokines, an ELR motif occurs in several members of the class, such as IL-8, Gro-␣, -␤, and -␥, and NAP-2, and confers proangiogenic activity to the cytokines (4,5,18,19). For example, IL-8 induces in vitro endothelial cell chemotaxis and in vivo corneal neovascularization (8).…”
Section: Huvec Chemotaxis In Response Tomentioning
confidence: 99%
“…All CXC chemokines, such as IL-8, that function as PMN chemoattractants have a conserved Glu-Leu-Arg (ELR) motif near the N terminus. The ELR motif is critical for PMN receptor binding and PMN activation (4,5). Human mini TyrRS also has an ELR motif that is conserved among mammalian TyrRSs (3).…”
mentioning
confidence: 99%